An Analysis of Translanguaging Practices in Sunny Dahye TikTok Video - Yanti, Ni Ketut Ayu Mira; Santosa, Made Hery; Ana, I Ketut Trika Adi (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Translanguaging is a sociolinguistic phenomenon that enables bilingual or multilingual speakers to utilize their entire linguistic repertoire to achieve communication goals. With the development of the digital era, this phenomenon has begun to shift to social media platforms such as TikTok. This study aims to identify the types of translanguaging used by Sunny Dahye in TikTok content and the frequency of their occurrence. This study employed an exploratory sequential mixed method design. Data were collected by selecting and watching videos, transcribing them, and identifying the types of translanguaging using an observation sheet. The findings of this study reveal that intra-sentential translanguaging is most frequently used in TikTok content, with the alternation involving longer elements such as phrases or clauses from English and Indonesian in a single sentence structure being the most common form of translanguaging used by the speaker. In addition, translanguaging is used as a communication strategy to express emotions, represent identity as a bilingual individual, and build engagement with the audience. The implications of this study suggest that language learners can utilize platforms such as TikTok to create bilingual content, which trains language skills and builds contextual meaning. Digital media can also be used as an alternative learning space outside of formal classrooms to encourage students to be more critical in improving their language skills and understanding, as well as to understand how language shift occurs, which can reflect cultural dynamics. Furthermore, this study enriches findings on language dynamics in digital spaces by showing that translanguaging is more than just a linguistic phenomeno.